Quality, Health, and Safety Assurance of Fish Produce based on the Republic of Indonesia’s Governmental Decree No. 57 of 2015 on the Quality, Health, and Safety Assurance of Fish Produce and the Increase of Fish Produce Value: A Sociophere Analysis in North Maluku - Absori Absori1, Muhammad Amin Hanafi2 , Khudzaifah Dimyati3, Natangsa Surbakti4, Siti Barora5 , Sury (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: This paper aims to describe the findings on quality, health, and safety guarantee of fish catch andthe related regulations in the Governmental Decree No. 57 of 2015. Method: This research uses the juridicalsociologic research method, with the descriptive qualitative approach, which describes the guarantee ofquality, health, and safety of fish catch based on the Governmental Decree No. 57 of 2015. Results: It isfound that there are violations in the form of an unhygienic method in processing the fish catch. In the FishAuction Center, the processing uses chemical substances which are prohibited for food. Conclusion: Thegovernment should make a policy which support the fishermen, so that they may use a safer and a healthiermethod in processing fish.